1998
DOI: 10.1159/000007115
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Glycolysis and Respiration of Sarcoma-180 Cells by Echitamine Chloride

Abstract: Malignant tumors are known to exhibit high rates of glycolytic activity leading to high production of lactic acid. Hence, neoplastic cells have elevated activity of enzymes responsible for glycolysis. Echitamine chloride, an indole alkaloid extracted from the bark of Alstonia scholaris, has been reported to have a highly promising anticancer activity against fibrosarcoma in rats. In the present study, the effect of echitamine chloride on energy metabolism of S-180 cells is investigated to have a better underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 22 publications
4
18
0
Order By: Relevance
“…The plants belonging to the family apocynaceae having anticancer properties like Adenium obesum, Ervatamia hycnea, Ochrasia elleptica, Rhazya stricta, Taberaemontana amygdalaefolia, Thevitia gaumer, and Vinca roseas have been reported to contain steroids and alkaloids (Sathyavathi et al, 1987;Graham et al, 2000). Cytotoxic studies with different fractions of ASE in the HeLa cells revealed best activity for ASERS followed by the ASE and ASECH, and the cytotoxic effect was better than that of ECL, a compound already reported to possess significant anticancer activity in vitro and in vivo (Saraswathi et al, 1997(Saraswathi et al, , 1998(Saraswathi et al, , 1999. This indicates that the observed anticancer activity of these fractions may be enhanced by the presence of certain other minor compounds in the extract and it may not solely be due to ECL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plants belonging to the family apocynaceae having anticancer properties like Adenium obesum, Ervatamia hycnea, Ochrasia elleptica, Rhazya stricta, Taberaemontana amygdalaefolia, Thevitia gaumer, and Vinca roseas have been reported to contain steroids and alkaloids (Sathyavathi et al, 1987;Graham et al, 2000). Cytotoxic studies with different fractions of ASE in the HeLa cells revealed best activity for ASERS followed by the ASE and ASECH, and the cytotoxic effect was better than that of ECL, a compound already reported to possess significant anticancer activity in vitro and in vivo (Saraswathi et al, 1997(Saraswathi et al, , 1998(Saraswathi et al, , 1999. This indicates that the observed anticancer activity of these fractions may be enhanced by the presence of certain other minor compounds in the extract and it may not solely be due to ECL.…”
Section: Discussionmentioning
confidence: 99%
“…was isolated from its alcoholic extract as described by Saraswathi et al (1997Saraswathi et al ( , 1998. The purity of the sample was confirmed by cochromatography, UV spectra and IR spectra and was compared with the authentic sample obtained from Dr. V. Mathurum, Captain Srinivasamurthy Drug Research institute for Ayurveda, Chennai, India.…”
Section: Isolation Of Echitaminementioning
confidence: 99%
“…Likewise, a dosage of 5 mg/kg regulated the altered levels of drug-metabolizing enzymes and microsomal hemoproteins in diseased mice. In this work, echitamine chloride was shown to alter the synthesis of apoproteins by incorporation of labeled phenylalanine [107].…”
Section: Pharmacological Studies On Isolated Alkaloidsmentioning
confidence: 99%
“…The in vitro viability of Ehrlich Ascites carcinoma cells was studied in the presence of a combination of echitamine chloride and vitamin A, since the latter has shown synergy in association with other anticancer drugs. The individual compounds displayed a weaker cytotoxic effect than a 200 to 10 µM combination of echitamine chloride and vitamin A as evidenced by corrected levels of lipid peroxides in plasma and studies on the incorporation of labeled thymidine in DNA [105]. The same researchers have investigated the cytotoxic effects of echitamine chloride in mice bearing S-180 solid tumor.…”
Section: Pharmacological Studies On Isolated Alkaloidsmentioning
confidence: 99%
See 1 more Smart Citation